Friction factors and rheological properties of orange juice - Telis-Romero, J.; Telis, VRN; Yamashita, F. (Elsevier B.V., 1999)
The rheological behavior of Brazilian orange juice with different water content (0.34-0.73 w/w) was studied at a wide range of temperatures (0.5-62 degrees C) using a concentric cylinder viscometer. The results indicated that the juices behave as pseudoplastic fluids with yield stress, being represented by the Herschel-Bulkley model. The rheological parameters were fitted as functions of both temperature and water content in the tested range. Based on dimensional analysis it was proposed a modified Reynolds number (Re-M), which includes the Herschel-Bulkley parameters. Experimental data of friction factors during heating and cooling processes of orange juice in laminar flow through circular tubes could be well correlated as a function of Re-M. (C) 1999 Elsevier B.V. Ltd. All rights reserved.